2013
DOI: 10.1016/j.infbeh.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Mother's and father's reports on their child's temperament: Does gender matter?

Abstract: Temperament ratings were obtained from 56 pairs of parents throughout the child’s first year to examine similarities and discrepancies in their report. Age, gender, stress, depression, and mother’s temperament were considered as factors possibly contributing to differences in the parents’ ratings of their child’s temperament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Interestingly, neither prenatal depression and gene expression nor their interaction were related to Regulation. Negative Affectivity and Regulation represent different constructs of temperament (Bayly & Gartstein, ; Gartstein et al., ) as measured by the IBQ‐R Negative Affectivity scale, which measures infants’ response to distress, fear, crying, and sad mood. The development of these temperament traits may be more likely to be influenced by the dysregulated HPA axis functioning in offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, neither prenatal depression and gene expression nor their interaction were related to Regulation. Negative Affectivity and Regulation represent different constructs of temperament (Bayly & Gartstein, ; Gartstein et al., ) as measured by the IBQ‐R Negative Affectivity scale, which measures infants’ response to distress, fear, crying, and sad mood. The development of these temperament traits may be more likely to be influenced by the dysregulated HPA axis functioning in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…The 14 subscales include activity level, cuddliness, fear, sadness, high‐intensity pleasure, low‐intensity pleasure, approach, smiling and laughter, falling reactivity, duration of orienting, perceptual sensitivity, distress to limitations, vocal reactivity, and soothability. The IBQ‐R has been found to form three hierarchical factors: Negative Affectivity, Regulatory Capacity/Orienting (Regulation), and Positive Emotionality/Surgency (Bayly & Gartstein, ; Gartstein, Bell, & Calkins, ). As prior evidence indicates that prenatal mood state is particularly associated with negative affectivity (Blair, Glynn, Sandman, & Davis, ; Pluess et al., ) and dysregulation (Babineau et al., ; Gutteling et al., ), we focused on the Negative Affectivity and Regulation factors, but not Positive Emotionality/Surgency.…”
Section: Methodsmentioning
confidence: 99%
“…Infant temperament may be important if parents of young children with more challenging behaviors use screen time as a distraction [ 24 ], for instance, it has been reported that infants whose mothers perceived them to be fussy or cry frequently, were more likely to watch television daily [ 17 ]. Both parenting style [ 25 ] and ratings of infant temperament [ 26 ] can differ between mothers and fathers, yet no studies appear to have evaluated media viewing in young children in relation to these characteristics assessed separately in both parents.…”
Section: Introductionmentioning
confidence: 99%
“…The literature also provides several factors that serve as protective influences against negative outcomes for parents and children. Parent's level of global self-esteem (i.e., self-esteem not tied to being a parent) has been found to be associated with parents' perceptions of their children's temperament (Bugental, Blue, & Cruzeosa, 1989;Chang et al, 2004), which has implications for parenting stress levels as parent perceptions of difficult child temperament has been linked with maternal stress (Bayly & Gartstein, 2013). While limited, research on this population has shown that adolescent mothers with higher levels of global self-esteem had lower levels parenting stress at later time points (Chang et al, 2004).…”
mentioning
confidence: 99%